Association Analysis of HIMP and SHIMP Quantitative Parameters in Patients With Vestibular Neuritis and Healthy Participants - Chen, Feiyun; Chen, Zichen; Zhang, Yuzhong; Wei, Xinyu; Zhao, Huandi; Hu, Juan; Cheng, Ying; Ren, Xiaoyong; Zhang, Qing (Frontiers in Neurology, 2021)
Background: The Head Impulse Paradigm (HIMP) and Suppression Head Impulse Paradigm (SHIMP) are objective, quantitative methods that directly test the vestibulo-ocular reflex (VOR) and are increasingly becoming a standard in evaluating patients with vestibular disorders. Objective: The main objective was to assess the correlations between HIMP and SHIMP parameters in patients with superior vestibular neuritis (VN) and normal subjects. Additionally, the correlations between the parameters of each method were analyzed. Methods: A retrospective cohort, non-randomized study was designed. HIMP and SHIMP were performed on 40 patients with VN and 20 normal subjects (40 ears). HIMP and SHIMP parameters were measured and calculated. Pearson and Spearman’s correlations were used to establish the associations among them. Results: A strong positive correlation was found between HIMP and SHIMP gain (Pearson’s r = 0.957, p = 0.000), while strong negative correlations were detected between HIMP and SHIMP saccade amplitudes (r = -0.637, p = 0.000) and percentages of covert saccades (r = -0.631, p = 0.000). In HIMP, strong and moderate positive correlations were identified between gain and saccade amplitude (R2 = 0.726, p = 0.000) and gain and saccade percentage (R2 = 0.558, p = 0.000), respectively. By contrast, an extremely weak positive correlation was observed between gain and latency (R2 = 0.053, p = 0.040). In SHIMP, strong and moderate positive correlations were found between gain and saccade percentage (R2 = 0.723, p = 0.000) and gain and saccade amplitude (R2 = 0.525, p = 0.000), respectively, but no correlation was detected between gain and latency (R2 = 0.006, p = 0.490). Conclusions: HIMP and SHIMP-related parameters were highly correlated (inter-method). Within each method (intra-method), moderate to strong correlations in VOR assessment were observed. These results further contribute to our understanding of the relationship between HIMP and SHIMP as well as to the diagnosis.